Asian Immigrant Women and their informal work in Canada: The Process of change - Agnes S. Thomas (Adult Education Research Conference, 2014)
Highly educated immigrant women from Asia choosing to work for cash in Canada is an indicator of the fact that their employment and economic outcomes are not positive. Drawing from the empirical study, this paper discusses the reasons for work choices and outcomes of this work on immigrant women.